Neonatal herpes simplex presenting as a zosteriform eruption. Issue 1 (19th January 2023) - Anderson, Elizabeth; Johns, Emma; Conlon, Joseph; Saleh, Ezzeldin
Abstract : Herpes simplex virus (HSV) infection in newborn infants is a potentially devastating disease leading to death and disability. Skin, eye and mouth (SEM) infections account for approximately half of the cases in the USA. The appearance of skin findings often guides clinicians towards early diagnosis of HSV infection, prompt interventions and life-saving management; however, less than half of neonates with proven disease present with characteristic vesicular lesions. Furthermore, if SEM infections are not treated promptly, there is significant risk of progression to central nervous system and disseminated disease. We present a case of HSV-2 infection in a neonate with an atypical zosteriform eruption on day 3 of life. This case demonstrates that neonatal HSV can unusually present in a zosteriform rash. By elucidating this unique presentation, we highlight atypical HSV skin presentation and emphasise on the importance of earlier diagnosis and antiviral treatment to prevent the associated morbidity and mortality.